Renal function after major uro-oncologic surgery and dexmedetomidine infusion - Novaes, Marcus Vinicius Martins; Lavinas, Paulo Sergio Gomes; Pires, Grace Haber Dias; Carvalho, Ana Claudia Geraldino de; Lopes, Renata Monteiro de Barros; El Dib, Regina [UNESP]; Nascimento Júnior, Paulo do [UNESP] (Scientific Research Publishing, 2013)
Objective: Acute kidney injury in major surgery is associated with increased postoperative mortality. This study aimed to evaluate renal function after major urologic surgery and intraoperative dexmedetomidine infusion. Methods: Thirty oncologic patients with normal renal function scheduled for prostatectomy or nephrectomy, anesthetized with combined epidural and general anesthesia, were randomized to receive either intraoperative blind infusion of dexmedetomidine (Dexmedetomidine Group, n = 15, 0.5 μg/kg load dose plus 0.7 μg/kg/h) or 0.9% saline (Control Group, n = 15) until the end of surgery. Intraoperative and cumulative 24-hour diuresis, serum creatinine (SCr), calculated creatinine clearance (ClCr) and serum cystatin C (SCys) at postoperative days 1, 2 and 3 and 2 weeks after surgery were evaluated. Results: Mean ± standard deviation values for intraoperative diuresis in Dexmedetomidine and Control Groups were 566 ± 396 mL and 298 ± 153 mL, respectively (p = 0.014). Cumulative 24-hour diuresis in Dexmedetomidine and Control Groups was 1947 ± 266 mL and 1748 ± 237 mL, respectively (p = 0.91). Mean values of SCr, ClCr and SCys were not significantly different from their baseline values in both groups and no significant differences were seen between groups at any moment for two weeks (p > 0.05). Conclusion: According to the doses used in this study, despite an intraoperative increase in diuresis, intraoperative infusion of dexmedetomidine did not influence renal performance up to two weeks after major uro-oncologic surgery, as evaluated by SCr, ClCr and SCys.
Keywords: Dexmedetomidine; Renal function; Nephrectomy; Prostatectomy; Epidural; General anesthesia